Is Follicle-Stimulating Hormone (FSH) Misnamed? Rethinking Its Role in Menopause as a Systemic Regulator of Bone, Brain, Metabolism, and Aging - Deanna Minich; Emily Hernandez; Caitlin Holmes; Douglas Lucas; Mona Fahoum; Wendy Warner; James Frame (Journal of Clinical Medicine, 2026)
Follicle-stimulating hormone (FSH) has long been recognized as a reproductive hormone in women and men. Based on research findings over the past decades, this classification may be incomplete and is increasingly being challenged. With this review, it is proposed that the name may be somewhat misleading. In addition to its presence in men without ovarian follicles, accumulating preclinical and clinical evidence suggests that FSH may serve as a marker of upstream endocrine changes across the stages of menopause. It may also participate in systemic processes that go beyond the classical hypothalamic–pituitary–gonadal axis. A less well-known finding is that FSH often rises before estrogen declines and is, to some extent, independent of estradiol. Moreover, changes in FSH levels through menopause coincide with considerable shifts in bone density, body composition, vascular function, neurobiology, and immune regulation. Based on what is known about FSH receptors, it is plausible that the systemic effects observed during menopause could result from extragonadal tissues’ receptivity to FSH. In this review, we present the traditional framework for FSH alongside recent findings that warrant re-evaluation of its function as a hormone, particularly in women as a modifiable marker of endocrine aging. We review clinical interventions for FSH, including laboratory biomarkers, hormone therapy, nutrition, botanicals, and lifestyle factors such as exercise and environmental exposures.